Book Review: Biodiversity, Biogeography and Nature Conservation in Wallacea and New Guinea (Volume 1) - Darman, Herman (Ikatan Ahli Geologi Indonesia, 2012)
Biodiversity, Biogeography and Nature Conservation in Wallacea and New Guinea (Volume 1)Edited byDmitry Telnov, Ph.D.Chairman of Coleopterology, The Entomological Society of Latvia Stopinunovads, Darzaiela 10, DZIDRINAS, LV-2130, Latvia / Lettland / LettonieWebsites: http://leb.daba.lv and http://www.zin.ru/Animalia/Coleoptera/eng/telnov.htm